Internal oxidation of Ni-Cr-Al alloys under various oxygen partial pressures at 1273 K - Ani, Mohd Hanafi; Herman, Sukreen Hana; -, Suryanto; Othman, Raihan (Trans Tech Publications, Switzerland, 2012)
Alloys for high temperature application always rely on their ability to form protective, dense Cr2O3 and Al2O3 scales. In case of Ni-Cr binary alloy, a minimum composition of Cr is required for the formation of continuous protective scale. However, addition of small amount of third element such as Al may results in decrease of required Cr composition to form protective scale. This study aims to clarify the effect of ternary element on the formation of protective scale quantitatively. Ni-Cr alloys composed with 2 mass% and 4 mass% of Al were exposed in oxidizing environment under Cr/Cr2O3, Fe/FeO and Ni/NiO oxygen partial pressure. The oxidation of all samples is following parabolic rate’s law. XRD and SEM results show that Al2O3 and Cr2O3 are formed internally. Parabolic rate’s constant of samples oxidized in Ni/NiO oxygen partial pressure is higher by few magnitude orders. Higher Al concentration decreases the parabolic rate’s constant. It is concluded that the formation of protective scale is enhanced by the addition of Al as ternary element in Ni-Cr alloys.